Analisis Determinan Kualitas Laporan Keuangan Kota Medan - Niken Wulandari; Suwarno Suwarno; Shella Pratiwi (CV. Ulil Albab Corp, 2024)
This study aims to analyze the Internal Control System and HR Competence as determinants of the quality of financial reports. The research approach used is the quantitative method. This study uses primary data obtained from a survey of respondents. The population consists of 129 employees of the Medan City Financial and Regional Asset Management Agency with a sample of 35 people after going through a purposive sampling technique. Data analysis consists of data quality testing, classical assumption testing and hypothesis testing. The results of the study indicate that analyzing the Internal Control System and HR Competence partially or simultaneously has a significant effect on the quality of financial reports.